2012
DOI: 10.1364/oe.20.027447
|View full text |Cite
|
Sign up to set email alerts
|

Three key regimes of single pulse generation per round trip of all-normal-dispersion fiber lasers mode-locked with nonlinear polarization rotation

Abstract: We show experimentally and numerically new transient lasing regime between stable single-pulse generation and noise-like generation. We characterize qualitatively all three regimes of single pulse generation per round-trip of all-normal-dispersion fiber lasers mode-locked due to effect of nonlinear polarization evolution. We study spectral and temporal features of pulses produced in all three regimes as well as compressibility of such pulses. Simple criteria are proposed to identify lasing regime in experiment. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
99
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(105 citation statements)
references
References 26 publications
4
99
0
2
Order By: Relevance
“…This is not the only possible mechanism for chaotic destabilization of the CPOs. In a number of recent works, fiber lasers operating in net-normal dispersion regimes have demonstrated noise-like and multi-state behavior [5,6,8,9], that was attributed to saturation of the SAM. These systems operated well in the positive dispersion with relatively small TOD, and produced completely different signatures, such as nearly symmetric spectra and bell-shaped autocorrelation traces with a narrow coherence spike at the top, thus allowing clear distinguishing from the To characterize the chaotic regime, we reconstruct the phase-space portrait for the experimental CDS dynamics based on the standard lag-delayed procedure [ Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not the only possible mechanism for chaotic destabilization of the CPOs. In a number of recent works, fiber lasers operating in net-normal dispersion regimes have demonstrated noise-like and multi-state behavior [5,6,8,9], that was attributed to saturation of the SAM. These systems operated well in the positive dispersion with relatively small TOD, and produced completely different signatures, such as nearly symmetric spectra and bell-shaped autocorrelation traces with a narrow coherence spike at the top, thus allowing clear distinguishing from the To characterize the chaotic regime, we reconstruct the phase-space portrait for the experimental CDS dynamics based on the standard lag-delayed procedure [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On top of that, the higher-order dispersion is often unavoidable in broadband systems. As a result, the CPOs are described by a quite complicated multidimensional parameter space; on practice one can often encounter increased amplitude or spectral noise, period multiplication and modulational instability, noise-like and chaotic behaviour [3][4][5][6][7][8][9]. It is important therefore to establish the physical mechanisms, properties, and find practical rules to help recognising such regimes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the NPR allows for fast saturable absorption. Recently, Smirnov et al [18] has demonstrated an allnormal-dispersion mode-locked fiber laser using the NPR technique that can support a large variety of outputs by adjusting the settings of the polarization controller (PC). Different PC settings yield different spectrum energies, durations, shapes, and widths.…”
mentioning
confidence: 99%
“…We present the phase-transition diagram among different regimes of chaotic emission in terms of the key cavity parameters: amplitude or phase turbulence, and spatio-temporal intermittency. In addition to short-pulse and cw emission regimes, ring fiber lasers used for passive mode locking via nonlinear polarization rotation exhibit the noise-like pulse emission mode of operation [1][2][3][4][5]. The resulting intense pulses have a broadband spectrum and low coherence length, which is of interest for metrology applications such as optical coherence tomography.…”
mentioning
confidence: 99%